Regulation of Oxidative Stress Response in Streptococcus pneumoniae : The Protective Role of RNase R - Prata, Sara Carrera (2024)
Streptococcus pneumoniae is a Gram-positive, aerotolerant opportunistic pathogen, recognised on the WHO’s priority list as the leading agent causing bacterial pneumonia. Our immune system responds by mobilising phagocytes that induce oxidative burst, generating reactive oxygen species (mainly H2O2, O2- and HOCl). Remarkably, this bacterium produces H2O2 and uses it as a competitive advantage against other pathogens. Paradoxically, S. pneumoniae lacks the main detoxifying enzymes, raising the question of how it handles oxidative stress. Previous results from our laboratory highlighted a key role of the exoribonuclease RNase R, in resistance to H2O2. RNase R is a solo member of the RNB family in S. pneumoniae and with the distinctive capability of degrading secondary RNA structures, suggesting a vital role in its metabolism. This work aims to unravel how RNase R promotes the survival of the pneumococcus under oxidative stress. Throughout this work, three pneumococcal strains were used, TIGR4 wild type, the isogenic mutant lacking RNase R (Δrnr), and the complemented strain expressing RNase R in trans (Δrnr+R). Beyond revisiting H2O2 effects, we performed susceptibility and viability assays to evaluate the effect of RNase R on the resistance to the other main oxidising agents of the oxidative burst, O2- and HOCl. On the other hand, to identify H2O2-induced genes and small non-coding RNAs (ncRNAs), RNA-sequencing was performed under H2O2 stress. The best candidates were experimentally validated via RT-qPCR and Northern blot. The results suggest that the strain lacking RNase R behaves differently depending on the stress challenge presented. The enzyme is critical in the resistance to hydrogen peroxide but does not seem to deeply affect S. pneumoniae resistance against superoxide anion and hypochlorous acid-induced stress. Moreover, we also observed higher lipid peroxidation in Δrnr under H2O2-induced stress, which is probably a result of our previous discovery that RNase R has an effect on membrane lipids. Under H2O2 oxidative stress, the genomic landscape was altered in Δrnr as compared to the WT, with 104 transcripts down- and 95 up-regulated in the mutant strain. Key affected genes include ABC transporters (piuBCDA, piaBA, mntE), regulatory elements (ciaR, glnR), DNA-binding proteins (yaaA), and enzymes (SP_1911, nanA). 19 transcripts were selected for validation, among which 17 had its expression variation confirmed by RT-qPCR and 5 were further studied by Northern blot. Globally, 58 ncRNAs were differentially expressed in the Δrnr strain under stress, 10 of which were identified for the first time in this study. Overall, our results offer new insights into the RNase R regulatory network and suggest that RNase R affects the levels of several transcripts with pivotal roles in the pneumococcus oxidative response. This suggests that RNase R might be a key enzyme in the complex and integrated network of mechanisms of the oxidative stress response, and we are only starting to uncover its role.